The effectiveness of different exercise mode interventions in improving disease activity in patients with ankylosing spondylitis: a network and dose-dependent meta-analysis - Ye, Guancheng; Gao, Luyuan; Liu, Chunping; Huang, Jian; Zheng, Xiaojia; Gao, Yingkai; Wang, Hao; Wang, Hailong (Frontiers in Physiology, 2026)
BackgroundAnkylosing spondylitis (AS) is a chronic inflammatory disease that impairs physical function, reduces quality of life, and is associated with psychological burdens such as anxiety and depression. While non-steroidal anti-inflammatory drugs (NSAIDs) and biologic therapies are standard treatments, exercise therapy is crucial for maintaining mobility and function. This study aimed to comprehensively compare the effects of 12 exercise interventions on AS patients’ disease activity and chest expansion (CE) via network meta-analysis (NMA) and dose-response meta-analysis, and explore dose-dependent effects to inform personalized exercise prescriptions.MethodologyFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, randomized controlled trials (RCTs) were searched from PubMed, Cochrane Library, Embase, and Web of Science until December 31, 2024. Eligible studies included adults with American College of Rheumatology/European League Against Rheumatism (ACR/EULAR)-diagnosed AS, comparing exercise with conventional treatment/placebo/no intervention, with outcomes of Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Metrology Index (BASMI), and CE. Two reviewers screened literature, extracted data, and assessed bias using the Cochrane Handbook. NMA and dose-response analysis (expressed as metabolic equivalents of task (MET) minutes/week) were performed (Prospero: CRD420251001511).ResultsThirty-two RCTs with 1757 participants were included. NMA showed hippotherapy simulation (HS) was most effective for reducing BASFI; aerobic exercise (AE) + Pilates was superior for BASDAI and BASMI; AE + Stretching Exercise (SE)+Supervise best improved CE. Dose-response analysis revealed non-linear relationships, with specific effective dose ranges identified for each outcome. Subgroup and sensitivity analyses confirmed result robustness.ConclusionExercise interventions, especially HS, AE + Pilates, and AE + SE + Supervise, effectively improve AS patients’ disease activity and CE. Non-linear dose-response relationships emphasize personalized prescriptions, providing evidence-based guidance for integrating exercise into AS management, with future large-scale RCTs needed to validate dose effects.